Analysis of Customer Loyalty in View of Company Commitment and Customer Trust in Traditional Life Insurance Products in South Tangerang - Erlita Kurniawaty; Nandan Lima Krisna; Jan Horas V. Purba (MultiTech Publisher, 2024)
The insurance services industry, as a trust-based business, is still considered not to have fully gained the trust of its customers, with decreasing customer loyalty in purchasing insurance products, especially traditional life insurance. The phenomenon observed in the research location indicates that customer trust in traditional life insurance products remains low, and the company’s commitment to providing product benefits is not yet optimal. This study aims to examine the influence of company commitment on customer loyalty through customer trust. The approach used in this research is a quantitative approach. The population and sample in this study consist of all customers holding traditional life insurance products in South Tangerang City, totaling 100 respondents, with a sampling technique using a saturated sample method. Research data were obtained from questionnaire responses and analyzed using SEM analysis methods with the assistance of Lisrel software. The study results indicate that (1) Company commitment has an effect on customer trust, (2) Customer trust influences customer loyalty, and (3) Company commitment affects customer loyalty through customer trust.